Association between Neck/Shoulder Pain and Trapezius Muscle Tenderness in Office Workers. (27th March 2014) - Brandt, Mikkel; Sundstrup, Emil; Jakobsen, Markus D.; Jay, Kenneth; Colado, Juan C.; Wang, Yuling; Zebis, Mette K.; Andersen, Lars L.
Abstract : Background . Neck/shoulder pain is a common musculoskeletal disorder among adults. The pain is often assumed to be related to muscular tenderness rather than serious chronic disease. Aim . To determine the association between neck/shoulder pain intensity and trapezius muscle tenderness in office workers. Methods . 653 employees from two large office workplaces in Copenhagen, Denmark, replied to a questionnaire on health and working conditions (mean: age 43 years, body mass index 24 kg·m −2, computer use 90% of work time, 73% women). Respondents rated intensity of neck/shoulder pain during the previous three months on a scale of 0–10 and palpable tenderness of the upper trapezius muscle on a scale of "no tenderness, " "some tenderness, " or "severe tenderness." Odds ratios for tenderness as a function of neck/shoulder pain intensity were determined using cumulative logistic regression controlled for age, gender, and chronic disease. Results . The prevalence of "no, " "some, " and "severe" tenderness of the trapezius muscle was 18%, 59%, and 23% in women and 51%, 42%, and 7% in men, respectively (chi-square, P < 0.0001). Participants with "no, " "some, " and "severe" tenderness of the trapezius muscle, respectively, rated their neck/shoulder pain intensity to 1.5 (SD 1.6), 3.8 (SD 2.0), and 5.7 (SD 1.9) for women and 1.4 (SD 1.4), 3.1 (SD 2.2), and 5.1 (SD 1.7) for men. For every unit increase in neck/shoulder pain intensity, the OR for one unit increase in trapezius tenderness was 1.86 (95% confidence interval 1.70 to 2.04). Conclusion . In office workers, a strong association between perceived neck/shoulder pain intensity and trapezius muscle tenderness exists. The present study provides reference values of pain intensity among office workers with no, some, and severe tenderness of the trapezius muscle.